No correlation between HSPG2 genetic variants and anthropometric characteristics within an ACL rupture risk modelling study - Lethabo Ramoshaba; Mary-Jessica Nancy Laguette; Malcolm Collins; Alison V September (Human Biology and Public Health)
Background Anterior cruciate ligament (ACL) ruptures are common musculoskeletal injuries, influenced by extrinsic and intrinsic factors such as genetic variations and anthropometric traits. While these factors contribute to ACL rupture susceptibility, their interactions are underexplored.